2019
DOI: 10.1071/py19022
|View full text |Cite
|
Sign up to set email alerts
|

Critical reflection for researcher–community partnership effectiveness: the He Pikinga Waiora process evaluation tool guiding the implementation of chronic condition interventions in Indigenous communities

Abstract: Critically reflecting on researcher–community partnerships is a key component in implementing chronic condition interventions in Indigenous communities. This paper draws on the results and learnings from a process evaluation that measures how well two research–community partnerships have followed the He Pikinga Waiora (HPW) Implementation Framework while co-designing chronic condition interventions in primary care. The HPW framework is centred on Indigenous self-determination and knowledge surrounded by commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The key elements of the HPW framework were integrated to support the design and development of the implementation programme. We completed a process evaluation that demonstrated consistency with the HPW principles and that were used for reflection to improve the process [47]. The evaluation suggested that there were strengths in the participatory process (i.e., community engagement and culture-centredness), with some improvements in end user engagement (i.e., integrated knowledge translation) and systems thinking to support the sustainability of the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key elements of the HPW framework were integrated to support the design and development of the implementation programme. We completed a process evaluation that demonstrated consistency with the HPW principles and that were used for reflection to improve the process [47]. The evaluation suggested that there were strengths in the participatory process (i.e., community engagement and culture-centredness), with some improvements in end user engagement (i.e., integrated knowledge translation) and systems thinking to support the sustainability of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Several partners commented that HPW principles are critical to achieving health gains for Māori communities. We built strong relationships and established trust which is a key outcome in and of itself [47]. Such relationships and trust take time and there needs to be sufficient co-design/participatory process to establish the relationship.…”
Section: Lessons Learntmentioning
confidence: 99%
“…It details the way in which this was done, and discusses the result, which is a new contribution to the literature in this area of work. Other literature stresses the importance of critical reflection in Aboriginal health, for example by encouraging researchers to reflect on power and privilege [24].…”
Section: Discussionmentioning
confidence: 99%
“…Much of this is directed at non-Aboriginal health professionals and includes guidelines [9,10], protocols [11,12], ethical principles [13] and suggested professional practices based on research and experience [14,15]. Authors highlight the need to work in partnership [16][17][18][19][20], be flexible [21], build relationships [17,21], get to know Aboriginal people [17,22] and reflect on their positions of privilege [23,24]. Programs often expand on the 'build relationships' principle to highlight that shared trust and respect are required in order to bring about sustained health change in Aboriginal communities [17,23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For the interviews, we have developed interview/focus group protocols around key HPW processes that will be utilised for this study [ 38 ]. We will also include questions that assess implementation needs for providers around capacity, funding, and health issues.…”
Section: Methodsmentioning
confidence: 99%